Poema de Chile de Gabriela Mistral: posibles metáforas de la infancia marica latinoamericana. - SUÁREZ GODOY, MATÍAS (Nomadías)
The figure of Gabriela Mistral has been a subject of debate for decades, mainly centered on the notions of mother, teacher, and poet. Today, various reinterpretations of her work have emerged, particularly from queer perspectives in Latin America, seeking to find within her texts spaces of metaphor and allegory that can give meaning to new ways of understanding Mistralian thought. In this exercise, a queer rereading of Poema de Chile is carried out, reflecting on the possible metaphors that can be drawn between the mother-child journey through Chilean territory and the mother-queer child journey of discovering and confronting sex-gender dissidence. In doing so, conclusions are drawn about the possibilities offered by Gabriela Mistral's writing in relation to queer experiences in the Latin American context.